The Effect of Work Experience and Incentives on Employee Performance with Motivation as a Mediating Variable at Bank Mandiri Gambir Branch - Winna Indriarti; Suharto; Muhammad Harri (Krisnadwipayana International Journal of Management Studies, 2025)
This study aims to: 1) determine the effect of work experience on employee performance, 2) determine the effect of incentives on employee performance, 3) determine the effect of work experience on motivation, 4) determine the effect of incentives on motivation, 5) determine the effect of motivation on employee performance, 6) determine the indirect effect of work experience on employee performance through work motivation, 7) determine the indirect effect of incentives on employee performance through work motivation. The research was conducted at Bank Mandiri Area Gambir with a sample of 80 respondents. The sampling technique used in this study was a saturated sample technique. The data analysis method used descriptive analysis and path analysis. The results of the study show that: 1) there is an effect of work experience on employee performance, 2) there is an effect of incentives on employee performance, 3) there is an effect of work experience on motivation, 4) there is an effect of incentives on motivation, 5) motivation has an effect on employee performance, 6) work experience has an indirect effect on employee performance through work motivation, 7) incentives have an indirect effect on employee performance through work motivation.